GAME MEDIA BASED ON LOCAL WISDOM TO IMPROVE PRIMARY SCHOOL STUDENTS' CRITICAL THINKING ABILITIES - Jatayu, Putri Dataliya; Nugroho, Wahyu; Pratiwi, Diyanti Jati (PROGRES PENDIDIKAN, 2024)
This research aims to analyze the effectiveness test of interactive game media using Educandy based on local wisdom to improve the critical thinking skills of class V students which include C4 (analyzing), C5 (concluding) and C6 (creating). The research method is Research and Development (RnD) with the ADDIE Model which consists of 5 stages, namely Analysis, Design, Development, Implementation and Evaluation. Data collection instruments are interviews, expert validation questionnaires, practitioner questionnaires, pre-test and post-test questions, teacher and student response questionnaires. Data analysis used Paired sample T-Test and N-Gain tests with the help of SPSS 26.00 software. The research data shows that the recapitulation of expert scores was 90.14% in the media, including the valid category, the expert practitioner results were 86.67%, including the very practical category, and the average teacher response score was 90%, while the students' results were 87.1. % which means very valid and interesting. The results of the Paired Sample T-Test and N-Gain different tests show a significance value of 0.00 or ≤ 0.05, which means there is a difference before and after the use of game media. So, it can be concluded that interactive game media uses Educandy based on local wisdom fulfills the categories of valid, practical and interesting to use in learning and is effective for improving the critical thinking skills of fifth grade elementary school students.